Effect of Sulfur Application on Spinach Phytoremedaiton Process of Cadmium in Contaminated Calcareous Soils - Ali Kasraian; Najafali Karimian; Ebrahim Pazira (آب و فاضلاب, 2012)
Recently, cadmium (Cd) concentration has increased in croplands through sewage sludge and phosphorous fertilizers application. On the other hand, some special methods, like phytoremedation, were introduced in order to decrease soil contamination hazard. Calcium carbonate plays an important role in Cd solubility in highly calcareous soils. Sulfurs oxidation, by dissolving Cd carbonate fraction, may improve phytoremediation efficiency. An experiment was conducted to study the effects of S application (equivalent to 0, 2, 4 and 6 Mg S ha-1) on Diethylene Triamine Pentaacetic Acid  (DTPA) extractable Cd and also on Cd uptake and extraction by spinach (Spinacea oleracea L.) in calcareous soils which were contaminated by 40mg Cd kg-1. To ensure biological S oxidation, all S-treated samples were inoculated by Thiobacillus spp. and incubated for 50 days. The soil pH, EC and soluble sulfate were affected by S application and it clearly showed that S oxidation process was occurred in Cd treated soils. The most significant change for pH and sulfate were observed at 4 Mg S ha-1 and for electrical conductivity (EC) of soil it occurred at 6Mg S ha-1. Application of S had no effect on DTPA extractable Cd in soils whereas; its concentration increased 73.55% in average in plant tissue. Plant dry matter decreased significantly (about 63 percent) following Cd application. Although the highest rate of S oxidation was observed at 4 and 6 Mg S ha-1 tٰٰٰhe maximum Cd extraction (2.5µg Cd pot-1) was observed at 2 Mg S ha-1 . This may be due to adverse effect of Cd toxicity and increase of soluble salt resulted by S oxidation in higher level of S application.